Dynamics of competing infectious agents in complex networks : a simulation study - Fan, Junkai (2013)
Complex networks exist everywhere in our daily life, including the Internet and different social relations. Inside these networks, there might be some competing infectious agents spreading among different individuals. Hence, the study of dynamics of competing infectious agents is becoming a popular research topic.